Mata Uang Kripto: Apakah Sebuah Jawaban Gaya Hidup Gen Z? - Palupi, Shara Merry; Putranti, Ellyn Citra (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
Gen “Z” is known for their ability to utilize technology that can be implemented in financial investment. This capability is what motivates Gen "Z" in Indonesia to invest by converting valuable assets into assets cryptocurrency. On this basis, this research was prepared to determine the characteristics of Gen "Z" in Indonesia who are investors cryptocurrency, to make this investment part of your lifestyle. This research uses a qualitative approach, focusing on examining the perceptions of the informants. The results of this research inform that Gen "Z" in Indonesia has chosen to invest in cryptocurrency pretty much. So that Gen "Z" in Indonesia has a high awareness of its importance financial investment and have an opinion that asset cryptocurrency be your best asset. This research can be used by the government as a basis for issuing regulations regarding asset management cryptocurrency, and can involve Gen "Z" in Indonesia to provide education to the public about digital financial investment.